Haemodynamic effects of pregnancy in patients with heart failure. Issue 5 (May 1982) - Blake, S; O'Neill, H; MacDonald, D
Abstract : Four patients, who were maintained on a constant regimen of treatment, developed congestive cardiac failure during pregnancy. They were examined regularly and carefully during the course of pregnancy to assess the progress of their failure. All four demonstrated unequivocal improvement during the third trimester attributable to obstruction of the inferior vena cava restricting venous return to the right side of the heart. This resulted in a fall in venous pressure in the neck and the resulting fall in right ventricular output could be very valuable in patients with left ventricular failure.